Antiviral Role of Serine Incorporator 5 (SERINC5) Proteins in Classical Swine Fever Virus Infection - Li, Wenhui; Zhang, Zilin; Zhang, Liangliang; Li, Hong; Fan, Shuangqi; Zhu, Erpeng; Fan, Jindai; Li, Zhaoyao; Chen, Wenxian; Yi, Lin; Ding, Hongxing; Chen, Jinding; et al. (Frontiers in Microbiology, 2020)
Serine incorporator 5 (SERINC5), a multipass transmembrane protein, protects cells from viral infections. The mechanism by which SERINC5 protects against classical swine fever virus (CSFV) infection is unknown. In this study, overexpression of SERINC5 in PK-15 and 3D4/2 cells significantly inhibited the growth of CSFV, whereas SERINC5 silencing enhanced CSFV growth. Additionally, CSFV infection reduced SERINC5 production in cells and tissues. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to identify and analyze protein and peptide molecules that potentially interact with SERINC5. A total of 33 cellular protein candidates were identified. Next, SERINC5 was shown to interact with melanoma differentiation-associated protein 5 (MDA5) by yeast two-hybrid, protein co-localization and co-immunoprecipitation assays. Furthermore, SERINC5 enhanced MDA5-mediated type I interferon (IFN) signaling in a dose-dependent manner. Our results suggest that the anti-CSFV effect of SERINC5 is dependent on the activation of the type I IFN, which may function along with MDA5. The inhibitory effect of SERINC5 on CSFV was disappeared when the endogenous expression of MDA5 was silenced using siRNA, suggesting that SERINC5 exerts an anti-CSFV effect in an MDA5-dependent manner. Our study demonstrated a novel link between SERINC5 and MDA5 in the inhibition of CSFV replication via the type I IFN signaling pathway.